La Violencia Intrafamiliar; sus efectos en el entorno familiar y social - Ocampo Enrique, Leonardo Jorge (2016)
This thesis entitled "Family Violence”. Its Effects on the Family and Environment " I developed considering that this is a sensitive issue that is affecting society and especially the family, since some time ago’s seen as a hidden item or as a purely family problem, these considerations need to be analyzed seriously and that the agencies in charge take urgent action to eradicate these shares on which violence and pain. In this regard it is important to emphasize that this issue involves situations containing barbaric actions that have resulted in mutilation or death of the abused (o). As an act of domestic violence that is especially related to abuse that supports female represented by women in the home or in some cases men and infringed the constitutional rights of the people , domestic violence becomes a social problem unlawful and that is part of the social, family and legal fields , so that brings the possibility for the development of this work and also for this purpose there is a broad conceptual information issued by different authors , attached to this has also served to support the research involving the use of electronic documents over use new information and communication technologies . The methodology used for the elaboration of this work relates to the type of applied research as a specific analysis of this problem was made by the inquiry to the affected source, as well as documentary approach literature as well as 6 field research by surveys, thus obtaining the possibility to verify and establish the expected results. Once completed this part of the work is manifest, using the Excel computer program, the results obtained from the survey of each of the items given in the interview and respective survey, leaving a record these results to the development of frequency tables and graphics cake type, containing these, relevant information as a result of the subject of this thesis. So I made this work investigating the historical origins of this action, stating definitions in the dictionary of the Royal Academy of the tongue and other dictionaries on different definitions of terms that are contained within the analysis also makes this family problem , then talk about the issue of family characteristics among other qualities, contain different definitions emitted who have tried and are trying is like society phenomenon from the issue of violence, characteristics, also makes the degrees of domestic violence, which is then analyzed aggression and its effects , its features, as well as how these events affect assaulted also consider grades experienced by the offender to reach the domestic violence, and also takes a generalized analysis of what this problem. Also, in order to test the hypothesis and analyze the relevance or otherwise of the objectives set forth herein, in this paper a survey and interview questions that relate to the topic is done, then proceed to analyze and expose manifest using templates and graphic percentages expressing the results. With the completion of this work I seek to the effects caused by these acts in the family and society to establish valid criteria that contribute to the prevention of this delicate problem.